Crazy - Lebert, Benjamin, 1982- (Köln : Goldmann Manhattan, 2001)
An English translation of the German novel about Benjamin Lebert, a sixteen-year-old with a disability who has been sent to a remedial boarding school where he embarks on a discovery of life, friends, love, booze, girls, and sex.
"Originally published in Germany as Crazy by Kiepenheuer & Witsch, Cologne, in 1999"--T.p. verso.
Keywords: Boarding schools -- Fiction; Friendship -- Fiction; Love stories; Man-woman relationships -- Fiction; Teenagers -- Fiction; German fiction -- Translation into English